The determinants of bicycle theft and robbery in the city of Bogotá, Colombia (2018)
Bicycle theft and robbery affects the number of bicycle users because since repetitive occurrence of these crimes may stop victims from bicycling. Interest on studying these particular crimes has grown in the past few years and studies have focused on analyzing preventive measures. Criminology theories have been the base for these stud-ies as these associate different factors of the environment and social behavior to the occurrence of criminal ac-tivities. This paper aims to analyze bicycle theft and robbery in the city of Bogotá, Colombia using a fixed effects Poisson model for panel data between 2014 and 2017. Different environment factors such as violent crimes, public amenities, land use features and socioeconomic attributes, were evaluated against the occurrence of these incidents within specified areas that divide the city. Results show that violent areas increase the risk of bi-cycles being stolen, as well as areas with a high number of bicycle racks and bus stations...